Makna Budaya pada Unsur-unsur Paralel dalam Tutur Adat Takanab - Antonius Nesi; Bernardus Tube (Universitas Medan Area, 2020)
This study aims to examine the cultural significance of parallel elements in Takanab customary speech. Takanab customary speech, in fact, is one manifestation of ritual communication in the Dawan community in Timor, East Nusa Tenggara. This type of traditional speech is unique because in it elements of language are presented in pairs (parallel), both between one word with another word in one line or between one line with another line in one stanza. Data collection is done by using the method of listening (linguistics) and ethnographic conversation (communication ethnography). Both methods are applied through record and note techniques. The data analysis method of this research is the extralingual equivalent method. Data analysis technique used is contextual analysis technique. Based on the data analysis, the results show that the cultural meaning in parallel lines in the Takanab traditional speech is the performance of ritual communication in the Dawan community environment which contains mutual cultural significance, socio-historical cultural meaning, cultural significance of religious life appreciation, and cultural meaning of reconciliation. The most parallel cultural meaning with the Takanab customary speech is the meaning of mutual cooperation and the cultural meaning of living religious life (religiosity).